Revitalisasi Sastra Lisan dan Pemertahanan Bahasa Daerah: Studi Kasus Sastra Lisan Rejung dan Guritan di Sumatera Selatan - Budi Agung Sudarmanto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
Abstract. South Sumatera has many oral literature. Rejung and guritan are two of them. In this article, two of those oral literatures are connected with literature revitalization and local language maintenance. Qualitative research is applied as the method. The result of discussion in this research is that revitalization of two oral literatures run well. Rejung Pesirah is one of a good rejung revitalisation results. Guritan is revitalized by performing current themes in order guritan is getting more accepted by community. Language maintenance can be done based on the place oral literature rejung and guritan use local languages, such as Enim, Semende, Besemah, Empatlawang, and Lahat.